Small businesses and effect of capital structure: A conceptual review - Kolandaisamy, I. (Serials Publications, 2017)
Small businesses are backbone of all countries developed and developing. They form substantial number of total businesses, contribute to Gross Domestic Production (GDP) and employment. This sector of economy plays significant role in economic development and growth of a country. Small or large business have their own capital structure i.e. the way firm's assets are financed. It can be equity or debt; it can also be a combination of both equity and debt. Most of the researches have discussed capital theories and determinants of capital structure in context of large firms. This paper discusses capital structure theories and determinants of capital structure theories in light of small businesses and determines that these can be applied on small businesses as well. © Serials Publications Pvt. Ltd.